Photodegradation of the Benzotriazine 1, 4‐Di‐N‐Oxide Hypoxia‐Activated Prodrug SN30000 in Aqueous Solution. Issue 11 (11th September 2014) - Gu, Yongchuan; Jaiswal, Jagdish K.; Wang, Jingli; Hicks, Kevin O.; Hay, Michael P.; Wilson, William R.
<x xml:space="preserve">Abstract</x> SN30000 is a benzotriazine di‐N‐oxide which is selectively toxic to radio‐resistant hypoxic cells in tumours. Given the complex photochemistry of some aromatic N‐oxides, we evaluated the potential for photodegradation of SN30000 solutions. Initial studies demonstrated significant oxygen‐insensitive degradation under normal laboratory lighting conditions. The kinetics of photodegradation showed marked concentration dependence of the form predicted by Beer's law, with a quantum yield of 0.016. The photoproducts could be rationalised as arising from an oxaziridine intermediate. The major stable product (cmpd 6; yield ∼50% of SN30000 loss under either UV or visible light) was characterised as resulting from intra‐molecular oxygen transfer to the morpholine side chain of SN30000. This mechanism is consistent with lack of formation of the corresponding morpholine N‐oxide from an analogue (SN29751) in which the proposed six‐membered‐ring transition state cannot form. Cmpd 6 was less cytotoxic than SN30000 to human tumour cells in culture, under either hypoxic or aerobic conditions, and was not toxic when administered intra‐peritoneally to NIH‐III nude mice at a dose (750 μmol/kg) above the maximal tolerated dose of SN30000 itself. In conclusion, SN30000 solutions are significantly photosensitive at low concentration, requiring protection from light, but the major photoproduct is less toxic than the parent. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3464–3472, 2014